Abdominal aortic aneurysms. (2nd May 2021) - Ahmed, Aadil; Heyes, Adam; Pandher, Jagraj; Rajagopalan, Sriram
Abstract : Vascular surgery is a relatively new surgical sub-speciality in the UK, with treatment of abdominal aortic aneurysms forming a substantial proportion of the emergency and elective caseload. This article summarises the guidance from the National Institute of Health and Care Excellence and the European Society for Vascular Surgery that outlines the epidemiology, diagnosis and management of abdominal aortic aneurysms. This is important for both vascular and non-vascular trainees to understand because of the critical nature of the disease, which can cause catastrophic haemorrhage, limb loss and mortality. However, if discovered in time, abdominal aortic aneurysms are a very treatable condition.